PEMBERDAYAAN UMKM UNTUK MENINGKATKAN PENDAPATAN MELALUI PEMASARAN ONLINE - Kurniati Kurniati; Daryyl Daryyl; Nicholas Nicholas (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
MSMEs are one of the sectors that provide great benefits for both the region and the community, with their ability to absorb a lot of labor, this sector answers the gap between the growth of the productive age population and the availability of jobs, besides that MSMEs also have a positive contribution in increasing the GDP of a region. Problems that are often found in the development of the MSME sector are marketing problems. One of the problems faced is the lack of knowledge about marketing related to the limited information that can be reached by microenterprises about the market. This also happenedto BOLU RASA MSMEs, which experienced many obstacles due to the pandemic and limited knowledge about online marketing. Conventional marketing that has been carried out so far has resulted in decreased sales and reduced income. Online-based marketing has not been widely understood and used by MSMEs. This service activity was carried out by the Untar PKM team in the form of training by providing examples of ways that businesses can use to market their products via the internet. Partners who participated in this activity there were 4 business people who were a branch of the Bolu Rasa Bakery UMKM. The practical contribution of this community service is to educate micro business owners to no longer hesitate to use social media in product marketing.